Anisotropic cellulose nanofibril composite sponges for electromagnetic interference shielding with low reflection loss. (15th January 2022) - Chen, Yiming; Luo, Heng; Guo, Hongtao; Liu, Kunming; Mei, Changtong; Li, Yang; Duan, Gaigai; He, Shuijian; Han, Jingquan; Zheng, Jiajia; E, Shiju; Jiang, Shaohua
Abstract: With the development of the electronic industry bringing convenience to people, a series of caused electromagnetic pollution problems (e.g., electromagnetic interference (EMI)) have recently also become urgent tasks. In this work, an anisotropic composite sponge consisting of cellulose nanofibrils (CNFs) and chemical co-precipitated silver nanowire (AgNW)@Fe3 O4 composites was successfully prepared. Due to the introduction of anisotropic structures and the synergistic effect among CNFs, AgNWs, and Fe3 O4, this composite sponge exhibited low density (16.76 mg/cm 3 ), good saturation magnetization (4.21 emu/g) and electrical conductivity (0.02 S/cm), and anisotropic EMI shielding ability. By adjusting the proportion (1:0.3) between AgNWs and Fe3 O4 and their loading (0.15 vol%) inside the sponge, the reflection loss of the sponge with the improved interface impedance mismatch was only 2.3 dB, accounting for 7.2% of the total loss. It is expected to become a promising EMI shielding material, especially for effectively alleviating the secondary reflection EM pollution. Graphical abstract: Unlabelled Image